2021
DOI: 10.1038/s41592-021-01309-x
|View full text |Cite|
|
Sign up to set email alerts
|

Community evaluation of glycoproteomics informatics solutions reveals high-performance search strategies for serum glycopeptide analysis

Abstract: Glycoproteomics is a powerful yet analytically challenging research tool. Software packages aiding the interpretation of complex glycopeptide tandem mass spectra have appeared, but their relative performance remains untested. Conducted through the HUPO Human Glycoproteomics Initiative, this community study, comprising both developers and users of glycoproteomics software, evaluates solutions for system-wide glycopeptide analysis. The same mass spectrometrybased glycoproteomics datasets from human serum were sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
94
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(97 citation statements)
references
References 73 publications
3
94
0
Order By: Relevance
“…However, each of these collision modes has advantages and disadvantages ( Riley et al, 2020 ). In terms of data processing, the annotation of intact glycopeptide MS/MS data is very challenging, including the correct assignment of glycan composition, glycosite as well as the peptide backbone ( Kawahara et al, 2021 ). Recently, many intact glycopeptides search engines have been developed based on modern MS techniques.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, each of these collision modes has advantages and disadvantages ( Riley et al, 2020 ). In terms of data processing, the annotation of intact glycopeptide MS/MS data is very challenging, including the correct assignment of glycan composition, glycosite as well as the peptide backbone ( Kawahara et al, 2021 ). Recently, many intact glycopeptides search engines have been developed based on modern MS techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Facilitated by the HUPO Human Glycoproteomics Initiative (HGI), Kawahara et al performed a comprehensive community-based evaluation of existing informatics solutions for large-scale intact glycopeptide analysis. Their study involved several high-performance search strategies and specified key variables that will help informatics decision making in glycoproteomics ( Kawahara et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, this algorithm was found to outperform GlycoPAT, GPQust, GlycXTool, among others, in terms of scoring O-glycoproteins and identifying high confidence O-glycopeptides. 29 Finally, Byonic is a commercially available software package for proteomic analysis and allows the user to define an unlimited number of variable modification types. It is currently considered the gold standard in glycoproteomics, though, recent work demonstrated that reported output from Byonic varied widely between groups using the same raw data.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, Protein Prospector and Byonic were determined to be high performing for O-glycoproteomics. 29 In this study, we performed a systematic comparison of six existing and recently released search algorithms for glycoproteomic data. To do so, we generated three samples that represent common glycoprotein preparations with increasing complexity, then searched the resulting MS data files.…”
Section: Introductionmentioning
confidence: 99%
“…Protein glycosylation, as one of the key protein posttranslational modifications, determines the function and metabolic pathways of glycoproteins. [1][2][3][4] Most studies have demonstrated that aberrant protein glycosylation is closely related to tumorigenesis and tumor metastasis; and many biomarkers found from biofluids and designed for cancer detection are glycoproteins. [5][6][7] In this regard, the large-scale characterization of glycosylation sites and glycoproteins could potentially provide a good opportunity for the early diagnosis and therapy of diseases.…”
Section: Introductionmentioning
confidence: 99%